Fine-tuning the cardiac O-GlcNAcylation regulatory enzymes governs the functional and structural phenotype of the diabetic heart. Issue 1 (8th February 2021) - Prakoso, Darnel; Lim, Shiang Y; Erickson, Jeffrey R; Wallace, Rachel S; Lees, Jarmon G; Tate, Mitchel; Kiriazis, Helen; Donner, Daniel G; Henstridge, Darren C; Davey, Jonathan R; Qian, Hongwei; Deo, Minh; et al.
Abstract: Aims : The glucose-driven enzymatic modification of myocardial proteins by the sugar moiety, β-N-acetylglucosamine (O-GlcNAc), is increased in pre-clinical models of diabetes, implicating protein O-GlcNAc modification in diabetes-induced heart failure. Our aim was to specifically examine cardiac manipulation of the two regulatory enzymes of this process on the cardiac phenotype, in the presence and absence of diabetes, utilising cardiac-targeted recombinant-adeno-associated viral-vector-6 (rAAV6)-mediated gene delivery. Methods and results : In human myocardium, total protein O-GlcNAc modification was elevated in diabetic relative to non-diabetic patients, and correlated with left ventricular (LV) dysfunction. The impact of rAAV6-delivered O-GlcNAc transferase (rAAV6-OGT, facilitating protein O-GlcNAcylation), O-GlcNAcase (rAAV6-OGA, facilitating de-O-GlcNAcylation), and empty vector (null) were determined in non-diabetic and diabetic mice. In non-diabetic mice, rAAV6-OGT was sufficient to impair LV diastolic function and induce maladaptive cardiac remodelling, including cardiac fibrosis and increased Myh-7 and Nppa pro-hypertrophic gene expression, recapitulating characteristics of diabetic cardiomyopathy. In contrast, rAAV6-OGA (but not rAAV6-OGT) rescued LV diastolic function and adverse cardiac remodelling in diabetic mice. Molecular insights implicated impaired cardiac PI3K(p110α)-Akt signalling as a potential contributing mechanism to the detrimental consequences of rAAV6-OGT in vivo . In contrast, rAAV6-OGA preserved PI3K(p110α)-Akt signalling in diabetic mouse myocardium in vivo and prevented high glucose-induced impairments in mitochondrial respiration in human cardiomyocytes in vitro . Conclusion: Maladaptive protein O-GlcNAc modification is evident in human diabetic myocardium, and is a critical regulator of the diabetic heart phenotype. Selective targeting of cardiac protein O-GlcNAcylation to restore physiological O-GlcNAc balance may represent a novel therapeutic approach for diabetes-induced heart failure. Graphical Abstract: